Simultaneous determination of centchroman and tamoxifen along with their metabolites in rat plasma using LC–MS/MS. (May 2015) - Rama Raju, Kanumuri Siva; Taneja, Isha; Singh, Sheelendra Pratap; Tripathi, Amit; Mishra, Durga Prasad; Hussain, K Mahaboob; Gayen, Jiaur Rahman; Singh, Shio Kumar; Wahajuddin, Muhammad
Aim: Tamoxifen and centchroman are two non-steroidal, selective estrogen receptors modulators, intended for long term therapy in the woman. Because of their wide spread use, there is a possibility of co-prescription of these agents.Materials & Methods : We studied the probable pharmacokinetic interaction between these agents in breast cancer model rats. A simple, sensitive and rapid LC-ESI-MS/MS method was developed and validated for the simultaneous determination of tamoxifen, centchroman and their active metabolites.Results: The method was linear over a range of 0.2–200 ng/ml. All validation parameters met the acceptance criteria according to regulatory guidelines.Conclusion: LC–MS/MS method for determination of tamoxifen, centchroman and their metabolites was developed and validated. Results show the potential of drug–drug interaction upon co-administration these two marketed drugs.